Evaluating the combined effect of neck muscle strength and hockey goaltender helmet liners in mitigating concussion risk during simulated horizontal head impacts - Renyard, N.; Kivi, D.; Sanzo, P.; Liu, M.; Zerpa, C. (ISBS Proceedings Archive (Michigan), 2023)
Concussions represent the second most common injury for ice hockey goaltenders. This study examined the combined effect of neck strength level and helmet liner type in mitigating concussion risk for ice hockey goaltenders. The researchers tested each helmet liner material statically for energy absorption capacity of the liner material, and dynamically by recreating concussion-causing events via head impact simulations for the risk of head injury criterion (HIC). The thermoplastic polyurethane (TPU) liner outperformed the standard vinyl nitrite (VN) liner during static testing and significantly reduced the HIC for high levels of neck strength (in newtons) during the repeated impact testing at the front, side, and back locations of the helmet. This information may facilitate the development of helmet liners composed of TPU and VN material across a range of neck strength levels to mitigate concussion risk for goaltenders.